Using metakaolin to improve the compressive strength and the durability of fly ash based concrete - Pacheco-Torgal, F. (2011)
Partial replacement of Portland cement by pozzolanic and cimentitious by-products or mineral additions that allow for carbon dioxide emission reductions is a major issue in the current climate change context. However, the use of low pozzolanic activity by-products like fly ash can cause a decrease relatively early in compressive strength. In this paper, the effect of metakaolin and fly ash on strength and concrete durability was investigated. The durability was assessed by different means of water absorption, oxygen permeability and concrete resistivity. Results show that partial replacement of cement by 30% fly ash leads to a decrease relevantly early in compressive strength, when compared to a reference mix of 100% Portland cement. Results also show that using 15% fly ash and 15% metakaolin replacement is responsible for minor strength loss but leads to outstanding durability improvement.